Closing the Loops in Biomedical Informatics From Theory to Daily Practice - Gaudinat, A.; Section Editor for the IMIA Yearbook Section on Closing the Loops in Biomedical Informatics (Yearbook of Medical Informatics, 2009)
Objectives This article presents the 2009 selection of the best papers in the special section dedicated to biomedical informatics and cybernetics.Method Synopsis of the articles selected for the IMIA yearbook 2009Results Five papers from international peer reviewed journals where selected for this section. Most of the papers have a strong practical orientation in clinical care. And this selection gives a good overview of what is done with “closing loop” approach, particularly during theyear 2008.Conclusion While quite mature for some clinical applications such as mechanical ventilation, it remains a challenge where rules for the decision system could be difficult to identify due to the number of variables. More complex systems with greater Artificial Intelligence approaches will certainly be the next trend for closed-loop applications.
Keywords: Closed-loop; clinical care; cybernetic; control theory; feedback